Dramaturgias do Futuro (Olhares, 2020)
The present article starts from regular observation of Free Play days of two groups of participanting chindren of Programa Curimim at Sesc Interlagos by a educator who is part of the socio-educational team of this Sesc São Paulo unit. During the investigation, the researcher was penetrated by pandemic and its developments linked by the necropolitical established in Brazil today. This article intend to emphasize a essencial caracteristc for the upcoming world after this calamity situation: the child’s state of Presence reached naturaly while plaing. This state will be essencial to the strength of bulinding a world to come. How it would be possible to learn from children, who lives this presence in a genuine form, how to achieve this state? Which are the colletive dramaturgies that we can write together from this state?
Keywords: Free Play; dramatics; Presence; Programa Curumim; Future